John Frankenheimer's the Train [videorecording (DVD)] - Coen, Franklin; Davis, Frank, 1897-1984; Lancaster, Burt, 1913-1994; Scofield, Paul, 1922-2008; Simon, Michel, 1895-1975; Flon, Suzanne, 1918-2005; Preiss, Wolfgang, 1910-2002; Munch, Richard; Moreau, Jeanne, 1928-2017; Tournier, Jean, 1926-2004; Wottitz, Walter; Jarre, Maurice; et al. (KL studio classics., 2015)
In August 1944, the Allied army is closing in on Paris. German commander and art fanatic Colonel Von Waldheim steals a vast collection of rare French paintings and loads them onto a train bound for Berlin. When a beloved French patriot is murdered while trying to sabotage Von Waldheim's scheme, Labiche, a stalwart member of the Resistance, vows to stop the train at any cost.